O parágrafo quarto da Octogesima Adveniens e a pastoral político-social - Andrade, Paulo Fernando Carneiro de (Revista eclesiástica brasileira, 2009)
This article deals with the question of the relation between Christians and the political social action in the light of the Apostolic Letter by Paul VI, Octogesima Adveniens, and of the paradigm of the relations between the Law and Morality, present in the Conciliar Decree Dignatis Humanae. At a time when the discussion of the possible relations between religion and politics in a plural democracy and in a lay State is back on the agenda, the present relevance of these two documents is very great. What are the limits, the possibilities and the demands for the Christian action in the politico-social sphere?